The prince of spies [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Hope and glory, 2022)
"Luke Delacroix has the reputation of a charming man-about-town in Gilded Age Washington, DC. In reality, he is secretly carrying out an ambitious agenda in Congress. His current mission is to thwart the reelection of Congressman Clyde Magruder, his only real enemy in the world. But trouble begins when Luke meets Marianne Magruder, the congressman's only daughter, whose job as a government photographer gives her unprecedented access to sites throughout the city. Luke is captivated by Marianne's quick wit and alluring charm, leading them both into a dangerous gamble to reconcile their feelings for each other with Luke's driving passion for vital reforms in Congress. Can their newfound love survive a political firestorm, or will three generations of family rivalry drive them apart forever?"--